SOSIALISASI TATA KELOLA DESA INKLUSI DI DESA TAMILOUW KECAMATAN AMAHAI KABUPATEN MALUKU TENGAH - Rolobessy, Mike Jurnida; Suatrat, Fatima; Sigmarlatu, Hendriyani; Tuasamu, Farah Desi (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Community service (PKM) with the theme "Inclusive Village Governance in Tamilouw Village, Central Maluku Regency" was implemented as an effort to increase the capacity of village officials and the community in understanding and applying the principles of inclusivity in village governance. The implementation of the service was carried out through two main stages, namely socialization and training on inclusive village governance, which took place in Tamilouw Village. This PKM stage used a social approach, field assessment, socialization and training. The methods used included material delivery, interactive discussions, case studies, and simulations of inclusion-based village planning. This service involved various elements of society, such as traditional leaders, religious leaders, village officials, women, youth, and representatives of vulnerable groups. Through this service, participants gained a deep understanding of the importance of participatory, transparent, and socially just village governance. The results of the service showed an increase in participants' knowledge, awareness, and practical skills in preparing inclusion-based village work plans and in identifying the needs of vulnerable groups. Furthermore, this community service program fosters a shared commitment and collective awareness to integrate inclusive principles into sustainable village development policies and practices. Overall, this PKM community service program contributes to strengthening inclusive and responsive village governance to community diversity and serves as a first step toward establishing equitable, participatory, and well-being-oriented village policies.